ANALISIS NILAI PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yuwaffa Muhammad Sulthan (2022)
This study aims to analyze the effect of profitability, investment decisions, leverage and inflation on firm value. The research uses a quantitative approach. Real estate sector companies while the sample used is 44 companies for the 2017-2020 period which were taken by purposive sampling method. The analytical method used is panel data regression analysis technique using Eviews 12 software. The results show that profitability and investment decisions have no effect on firm value, while leverage and inflation have a positive effect on firm value.